1981
DOI: 10.1007/bf00254508
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic phase, reflex insulin secretion neuroanatomical and physiological characterization

Abstract: Using chronically catheterized, freely moving male Wistar rats, we have shown that the sweet taste of a saccharin solution reliably triggers a rapid cephalic phase insulin response (CPIR), in the absence of any significant change of glycemia. To establish the neural mediation of this reflex response we used rats that were cured from streptozotocin diabetes by intrahepatic islet-transplantation as a denervated B-cell preparation. The complete lack of any saccharin-induced CPIR in these rats suggests that it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
1
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(113 citation statements)
references
References 41 publications
5
105
1
2
Order By: Relevance
“…Examples of such glucose-sensing systems include the taste bud cells. These express the sweet taste receptors (T1R2/T1R3) [1], which detect the presence of sugar in the food and initiate nervous responses to control the cephalic phase of insulin secretion, as well as food preference [2,3]. In hepatocytes, high glucose concentrations activate the transcription factor known as carbohydrate response elementbinding protein (ChREBP), a key inducer of glycolysis and lipogenesis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such glucose-sensing systems include the taste bud cells. These express the sweet taste receptors (T1R2/T1R3) [1], which detect the presence of sugar in the food and initiate nervous responses to control the cephalic phase of insulin secretion, as well as food preference [2,3]. In hepatocytes, high glucose concentrations activate the transcription factor known as carbohydrate response elementbinding protein (ChREBP), a key inducer of glycolysis and lipogenesis [4].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This variability has enabled investigators to identify measures in adult rats, at normal body weight, that can accurately and reproducibly differentiate distinct subgroups that are obesity-prone (OP) or obesity-resistant (OR). These markers of obesity include initial weight gain during the first few days on a high-fat diet, 1,8 levels of leptin after a single high-fat meal in rats maintained on a lab chow diet, 9 meal-induced release of insulin 10 and fasting levels of triglycerides or basal growth hormone secretion in rats on chow. 11,12 While still at normal weight, the OP rats are found to exhibit a phenotype that has similarities to that seen in adult rats after they have become obese.…”
Section: Introductionmentioning
confidence: 99%
“…1B and D), the cephalic phase insulin secretion, is well documented in non-ruminants including humans (Strubbe & Steffens, 1975;Berthoud et al 1980Berthoud et al , 1981Berthoud & Jeanrenaud, 1982;Strubbe, 1992;Teff et al 1995) and in ruminants (Bassett, 1974;Bhattacharya & Alulu, 1975;Chase et al 1977;Porter & Bassett, 1979;Vasilatos & Wangsness, 1980;Faverdin, 1986). However, the observation (Figs 1 and 2) that vagotomy suppresses the secretion of insulin that occurs immediately after the start of eating, has not been reported previously for ruminants.…”
Section: Electrical Stimulation Testsmentioning
confidence: 99%
“…CPIR is well documented in non-ruminants, including humans (Berthoud et al 1980(Berthoud et al , 1981Berthoud & Jeanrenaud, 1982;Strubbe, 1992;Teff et al 1995) and ruminants (Bassett, 1974;Bhattacharya & Alulu, 1975;Chase et al 1977;Vasilatos & Wangsness, 1980;Faverdin, 1986). It has been suggested that CPIR is one of a group of physiological responses that occur after activation of the vagus nerve through food-related sensory stimulation (Berthoud et al 1981;Taylor & Feldman, 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation